THE REGIONAL GOVERNMENT’S POLICY IN INCREASING THE REGIONAL ORIGINAL INCOME THROUGH RETRIBUTION TARIFF COLLECTION OF PUBLIC TRANSPORTATION AND THE LIKE - Ahmad Lanang Citrawan; Rully Syahrul Mucahrom (Universitas Muhammadiyah Ponorogo, 2019)
Regional autonomy essentially pushes the regional government to take care of its own region’s affairs. In the regional autonomy, the orientation in its development is surely based on the region’s potentials in various aspects and legalities to push the region’s potential of productivity. One of the reasons is so that the region may be advanced in the aspect of development. It cannot be denied that online transportations – both those which are two-wheeled or four-wheeled – have become a trend in the society as it has the advantage of an eased system. With this ease, there needs to be strategic policies in the form of regional government policies to increase the region’s potentials especially in the aspect of regional retribution through the public transportations provided by the transportation companies. This is so that the Regional Original Income may increase. This regulation is hierarchic. Thus, it gives the regional government to form a policy regarding the collection of regional retribution through public transportation services. This may increase the Regional Original Income in the framework of regional autonomy. This research uses a normative approach to analyze the region’s potentials to collect regional retribution through public transportation services, and it is regulated in the Constitution No. 28 of 2009 regarding Tax and Regional Retribution